Limitní parametry technologie ohýbání dílců z trubek - Maleček, Michal (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
Ohýbání trubek je dnes v průmyslu často používanou metodou. Avšak po dlouhou dobu byla limitována řadou defektů. Předkládaná práce se zabývá studií vlivu poloměru ohybu a tloušťky stěny na kvalitu ohybu. Praktická část práce zahrnuj experimentální ohyby trubek. Dále je v práci řešeno stanovení skutečných hodnot tloušťky stěny, ovality, tvaru ohybu, průřezového modulu v ohybu a neutrální osy trubky. Na základě vyhodnocených kritérií jsou pak stanoveny přípustné parametry ohybu.

Currently, rotary draw bending is frequently used method in industry. Nevertheless, it has been limited for long time by different types of defects. Submitted thesis deals with the study of the influence the bending radius and wall thickness on the quality of bent. Practical part of the thesis includes experimental rotary draw bending of tubes. The work also solves determining actual values of the wall thickness; ovality, bent shapes, the section modulus in bending and the neutral axis of the tube On the basis of evaluation of criteria are then set the parameters of permissible bend
Forming limits for the bending process of tubular components
Keywords: Ohýbání navíjením; trubky; parametry ohybu; Rotary draw bending; tubes; bending parameters